Early Listening Skill on Lesson Study-Based Activities - Farida Samad; Rosita Wondal; Nurhasanah Nurhasanah (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This study aimed to describe children's listening skills in lesson study-based learning activities at Telkom preschool group B1 in Ternate City. The students involved were 24 early students. The lesson study process included preparing, observing, and reflecting lessons in the context of listening skills. In data analysis, Miles and Huberman interaction model was employed to describe the data qualitatively and quantitative data analyzed using descriptive statistics. The results showed that children listening skill on lesson study-based learning activity on the ‘market day’ topic implemented at Telkom Preschool Group B1 in Ternate City was categorized as good (81.8) and sufficient (68.2). Furthermore, the data the development of a non-cognitive assessment instrument for listening ability in early childhood based on lesson study is feasible to be implemented .The result can be used as a basis for improvement and strengthening a lesson study activities dealing with listening skills in preschool that lesson study-based activities can improve children early listening skills in understanding subjects on the theme ‘market day’.